2023
DOI: 10.1177/00472875231175079
|View full text |Cite
|
Sign up to set email alerts
|

Animal Ethics and Tourism: Deepening a Stimulus–Organism–Response (S-O-R) Framework

Abstract: Animal ethics has been recognized as an emerging issue in tourism, but limited research has concentrated on tourists’ behaviors toward animal ethics and its fundamental mechanisms. This study develops a research framework to address this gap, including media coverage and organizational strategies on reducing animal abuse, cognitive and affective states toward animal ethics, norm activation model variables, and behavioral intentions using stimulus–organism–response (S-O-R) theory. Findings indicate that media c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 106 publications
1
2
0
Order By: Relevance
“…In line with Han (2014), awareness of consequences (AC) was found to positively affect ascription of responsibility (AR), and subsequently influenced moral norms (MN). These results strengthen and verify the NAM framework (Fakfare et al, 2024a), particularly in the food truck context. Furthermore, it was found that anticipated emotions, particularly in terms of feelings of pride were influenced by AC and AR.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In line with Han (2014), awareness of consequences (AC) was found to positively affect ascription of responsibility (AR), and subsequently influenced moral norms (MN). These results strengthen and verify the NAM framework (Fakfare et al, 2024a), particularly in the food truck context. Furthermore, it was found that anticipated emotions, particularly in terms of feelings of pride were influenced by AC and AR.…”
Section: Discussionsupporting
confidence: 79%
“…In terms of practical implications, the contextualization of NAM constructs and their application within the sustainable food truck context offers valuable insights for practitioners and policymakers. Firstly, by understanding how moral norms, anticipated feelings of pride, and responsibility attribution influence consumer behaviors, food truck operators can tailor their strategies to promote sustainable practices effectively (Fakfare et al, 2024a). This may involve initiatives such as offering eco-friendly packaging options, implementing waste reduction measures, and communicating the environmental benefits of such actions to customers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation